Functionalization of 3-Chlorobenzaldehyde - Aksjonova, Kristine; Belyakov, Sergey; Liepinsh, Edvards; Boman, Arne; Lundstedt, Torbjorn; Lek, Per; Trapencieris, Peteris (Synthesis, 2012)
2-Substituted 3-chlorobenzaldehydes were prepared from the corresponding 2-(3-chlorophenyl)-1,3-dioxolanes using an ortho-lithiation strategy. The 6-chloro-2-formylbenzamide exists only in a ring form, but 6-chloro-2-formylbenzoic acid esters were isolated in both forms as open chain and cyclic tautomers. 7-Chloro-3-hydroxy-3H-isobenzofuran-1-one reacted with nucleophilic reagents at the carbonyl or quaternary carbon depending on the character of nucleophile.
Keywords: 3-chlorobenzaldehyde; 2,3-dihydroisoindol-1-ones; 3H-isobenzofuran-1-ones; directed ortho-lithiation; ring-chain tautomers